Demand Curves for Animal Consumers - Kagel, John H.; Battalio, Raymond C.; Rachlin, Howard; Green, Leonard (Quarterly Journal of Economics, 1981)
Results are reported from experiments showing that both income-compensated and ordinary (uncompensated) demand curves for nonhuman consumers are negatively sloped. Essential commodities are determined to be gross complements, while nonessential goods are independent or gross substitutes. The experiments extend the concepts underlying value theory to nonhumans and provide a basis for intensive experimental investigations of additional aspects of the theory.